OC-059 TEMPORARY ABDOMINAL CLOSURE NEGATIVE THERAPY IMPROVES DEFINITIVE FASCIAL CLOSURE RATES IN PATIENTS WITH OPEN ABDOMEN MANAGEMENT. (13th October 2022) - Bannon, A; Leatherby, R; Birtles, L; Augustine, T; Moinuddin, Z; Van Dellen, D
Abstract: Aims: Encapsulating peritoneal sclerosis (EPS) is a rare phenomenon characterised by encasement of the bowel by a thickened peritoneum due to prolonged peritoneal dialysis exposure. We are an international referral centre, typically managing cases with a planned open abdomen (OAM) and scheduled relook after 24–48 hours. We compare outcomes for those patients whose OAM was with simple packing (betadine-soaked-gauze) with negative pressure therapy providing temporary abdominal closure (TAC). Methods: A retrospective review of a contemporaneous database of patients who underwent surgery for EPS between 2010–2020 was performed. Primary endpoints were time to definitive closure and closure method (primary fascial closure vs. bridged biologic mesh closure vs. failure to close fascia). Secondary endpoints included comparison of stoma formation, bowel resection, fistulation rate, enterotomy formation, re-operation post closure, and wound infection. Results: 99 patients had OAM (56 static packing; 43 TAC.) Patients with TAC were significantly more likely to undergo primary closure of fascia when compared to those patients managed with static packing, (63% vs 13%, p<0.0001, Chi Sq). The TAC group required fewer theatre episodes (n=2.27 vs. 4.78, p<0.0001, t-test) and time in days to achieve closure (n=2.78 vs n=4.68, p<0.005, Chi Sq), with less failure to close episodes and returns to theatre 30 days post closure. Conclusion: This study provides definitive evidence of TAC efficacy for fascial closure following OAM. This provides definitive benefit over traditional open abdominal methods. It may provide benefit in definitive open abdominal management in other areas (sepsis and trauma) and requires further study.